Survival of Salmonella enterica in Freshwater and Sediments and Transmission by the Aquatic Midge Chironomus tentans (Chironomidae: Diptera) - Moore, Barry C. (American Society for Microbiology, 2003)
Survival of a nalidixic acid-resistant strain of Salmonella enterica serovar Typhimurium mr-DT-104 in water and sediments was tested using artificially contaminated aquaria. Water samples remained culture positive for salmonella for up to 54 days. Sediment samples were culture positive up to 119 days. In addition, potential mechanisms for spreading salmonella in the environments by chironomid larvae and adults were tested. We evaluated the acquisition of mr-DT-104 by chironomids from contaminated aquatic sediments and subsequent spread to uncontaminated sediments. Larval chironomids raised in contaminated sediments became culture positive, and the bacteria were carried over to adults after emergence. Contamination of clean sediments by chironomid larvae was not demonstrated. These findings clearly suggest that mr-DT-104 serovar organisms can survive in aquatic sediments for at least several months. Uptake of salmonellae by chironomid larvae and adults suggests that they are possible vectors of mr-DT-104 in both aquatic and terrestrial environments, although the role of larval defecation in movement of bacteria to new sediments was not demonstrated.